1980
DOI: 10.1111/j.1365-2559.1980.tb02923.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous lesions in nasal biopsies

Abstract: A series of 19 cases has been reviewed in which biopsy of an intra-nasal lesion revealed a granulomatous pathology. These have been classified on an aetiological basis. They include infections, Wegener's granuloma and neoplasms with a granulomatous stroma. One patient with sarcoidosis first presented with lesions in the nasal cavity. Cholesterol granulomata were seen in four lesions removed from the paranasal sinuses. In six cases clinical and histological examination failed to show a cause for the granulomata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Cholesterol granuloma is a recognised but rare lesion of man occurring in enclosed bony spaces such as the orbit, paranasal sinuses and middle ear (Nicholls 1956, Graham and Michaels 1978, Sade 1979, Coup and Hopper 1980, Parke and others 1982. The terms cholesteatoma and choleterol granuloma have been used interchangeably in the past but cholesteatoma is now taken to imply the presence of ectopic epithelial elements and hence a different aetiology and the terms are now distinguished (Sade 1979, Parke and others 1982).…”
Section: ~~ ~mentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol granuloma is a recognised but rare lesion of man occurring in enclosed bony spaces such as the orbit, paranasal sinuses and middle ear (Nicholls 1956, Graham and Michaels 1978, Sade 1979, Coup and Hopper 1980, Parke and others 1982. The terms cholesteatoma and choleterol granuloma have been used interchangeably in the past but cholesteatoma is now taken to imply the presence of ectopic epithelial elements and hence a different aetiology and the terms are now distinguished (Sade 1979, Parke and others 1982).…”
Section: ~~ ~mentioning
confidence: 99%
“…Describing cases in the paranasal sinuses Graham and Michaels (1978) and Coup and Hopper (1980) noted a close association with haemorrhage and concluded that this was the main initiating factor. Coup and Hopper (1980) found an apparent association with nasal polyps but Graham and Michaels (1978) found no common cause for the haemorrhage in their cases. In this dog no polyps were present and no abnormal haemorrhage was seen at the time of surgery.…”
Section: ~~ ~mentioning
confidence: 99%
“…We have reviewed 116 recorded cases of generalized sarcoidosis in which granulomas were found clinically in the nasal cavities and histologically confirmed (Ulrich, 1918 ;Allison and Mikell, 1932;Novy, 1936;Kistner and Robertson, 1938;Seifert, 1939;Poe, 1940 a andb, 1942, the same case being reported later by Poe and Seager, 1950;Bordley and Proctor, 1942;Wille, 1946;Rubin and Kling, 1948 ;Robinson and Pound, 1950, Case 13;Larsson, 1951, Cases 7, 8, 9 and 10;Lindsay and Perlman, 1951 , nine cases;Livingstone, 1956;Ferguson and Paris, 1958, Case 5;Weiss, 1960, three cases;Creston and Dibble, 1961 ;Arova, 1963 ;Siltzbach and Blaugrund, 1963, six cases;Kämpfer, 1964, ten cases;Dowie, 1964, three cases; 292 Sarcoidosis Black, 1966 ;Scadding, 1967, three cases;Mckelvie et al, 1968, 11 cases;Page and Seth, 1969;Di Benedetto and Lefrak, 1970;Carosso, 1974;Wright et al, 1974, two cases;Gordon et al, 1976, three cases;Kirschner et al, 1976;Neville et al, 1976, 17 cases ;Delaney, 1977, Case 1;Selroos and Niemistö, 1977, 11 cases;Maillard and Goepfert, 1978;Allen, 1979;Som and Krespi, 1979;Coup and Hopper, 1980;Hammond and Kataria, 1980). Of the cases in which the sex of the patient was mentioned, 73 were in women and 25 in men; ...…”
Section: The Nosementioning
confidence: 99%
“…In a review of 19 unsel ected cases in which nasal biopsies showed granulomatous changes, Coup and Hopper (1980) found that the final diagnosis was sarcoidosis in only one; it was tuberculosis in two, leprosy in one, Wegener 's granuloma in three, choJesterol granuloma in four, unusual rnalignant neoplasms in rwo, and in six 'idiopathic granuloma '. In the latter group, of wh ich three involved the post-nasal space, no evidence of generalized granulomatosis was found, and the local condition resolved or improved under observation. The categorization as sarcoidosis of granulomas in the nose, as in other locations, depends not only upon their histology but also upon acceptable evidence that they are part of a widespread noncaseating epithelioid cell granulomatosis (Chapter 26) .…”
Section: Differential Diagnosis Of Naso-pharyngeal Granulomasmentioning
confidence: 99%
“…We discuss the diagnostic and subsequent therapeutic problems in the management of the midline necrotizing lesions. as infections, neoplasms and Wegener's granulomatosis (3,4).…”
mentioning
confidence: 99%